Morningstar Ratings and Mutual Fund Performance - Blake, Christopher R.; Morey, Matthew R. (Journal of Financial and Quantitative Analysis, 2000)
This study examines the Morningstar rating system as a predictor of mutual fund performance for U.S. domestic equit funds. We also compare the predictive abilities of the Morningstar rating system with those of alternative predictors. The results indicate findings that are robust across different samples, ages and styles of funds, and performance measures. First, low ratings from Morningstar generally indicate relatively poor future performance. Second, there is little statistical evidence that Morningstar's highest-rated funds outperform the next-to-highest and median-rated funds. Third, Morningstar ratings, at best, do only slightly better than the alternative predictors in forecasting future fund performance.